Effect of website performance expectancy on customer satisfaction: online fashion performance - Amoriom, M.; Loureiro, S. M. C. (2017 Global Fashion Management Conference, 2017)
This study builds on prevalent approaches of extending the applications of importance performance analysis (IPA) tool. Thus, we analyse the influence of Performance expectancy on Customer Satisfaction. The instruments employed were adapted from previous studies and pilot tested with a group of master students to verify clarity of meaning and comprehension. Findings reveal the stronger influence of three factor that emerge from performance expectancy: Usability, Reliability, Information Quality.